"What about China?" and the threat to US–Russian nuclear arms control. (3rd July 2020) - Allison, David M.; Herzog, Stephen
ABSTRACT: The administration of President Donald J. Trump has consistently used fear of China to undermine nearly five decades of bipartisan consensus on US–Russian nuclear arms control. The negative consequences of these actions may last far beyond the Trump presidency. If generations of agreement between Democrats and Republicans on bilateral nuclear treaties with Russia erode, it will pose a significant setback to US national security and global stability. Future leaders may ultimately need to consider new approaches to nuclear risk reduction that preserve the benefits of the arms control regime.